The Pathoconnectivity Profile of Alzheimer’s Disease: A Morphometric Coalteration Network Analysis - Manuello, Jordi; Nani, Andrea; Premi, Enrico; Borroni, Barbara; Costa, Tommaso; Tatu, Karina; Liloia, Donato; Duca, Sergio; Cauda, Franco (Frontiers in Neurology, 2018)
Gray matter alterations are typical features of brain disorders. However, they do not impact on the brain randomly. Indeed, it has been suggested that neuropathological processes can selectively affect certain assemblies of neurons, which typically are at the center of crucial functional networks. Because of their topological centrality, these areas form a core set that is more likely to be affected by neuropathological processes. In order to identify and study the pattern formed by brain alterations in patients’ with Alzheimer’s disease (AD), we devised an innovative meta-analytic method for analyzing voxel-based morphometry data. This methodology enabled us to discover that in AD gray matter alterations do not occur randomly across the brain but, on the contrary, follow identifiable patterns of distribution. This alteration pattern exhibits a network-like structure composed of co-altered areas that can be defined as co-atrophy network. Within the co-atrophy network of AD, we were able to further identify a core subnetwork of co-altered areas that includes the left hippocampus, left and right amygdalae, right parahippocampal gyrus and right temporal inferior gyrus. In virtue of their network centrality, these brain areas can be thought of as pathoconnectivity hubs.